Parental preferences for sex of children in Nigeria: Cultural influences and family structure - Alex Bawuah; Michael Sarfo; Godness Kye Biney; Francis Appiah; Linus Baatiema; Sanni Yaya (PLoS ONE, 2025)
Background Nigeria is characterized by deeply rooted traditional practices that often amplify gender bias. Despite this, there is limited research examining the relationship between cultural and family characteristics and parental sex preference in Nigeria. To address this gap, we investigated how cultural factors and family structure is associated with parental sex preferences in the country. Methods This study utilized data from the 2018 Nigeria Demographic and Health Surveys (NDHS). Parental sex preference for children served as the outcome variable, while family structure and cultural background were the explanatory variables. Descriptive analyses, including frequencies, percentages, and cross-tabulations, were used to characterize the sample. Due to the unordered categorical nature of the outcome variable, a multinomial logistic regression model was employed to assess the impact of culture and family structure on parental sex preference. Results A higher proportion of women preferred more girls compared to men (15.64% vs 6.85%), while more men expressed a preference for boys than women (52.48% vs 26.2%). Men with more sons were significantly more likely (RRR = 1.48, 95% CI = 1.23–1.78) to prefer more boys over an equal number of boys and girls, compared to men with equal numbers of sons and daughters. Similarly, women with more sons were more likely (RRR = 1.60, 95% CI = 1.45–1.77) to prefer more boys rather than an equal number of boys and girls, compared to women with equal numbers of sons and daughters. Conclusion These findings shed light for understanding gender dynamics and informing policies that promote gender equality and balanced family structures. Such policies are critical for enhancing family planning practices and advancing the Sustainable Development Goals (SDGs) by 2030. With only six years left to meet these targets, we urge all stakeholders to collaborate and intensify efforts to drive meaningful progress.